Impact of Gadget Use on Emotional Development of Children Aged 5-6 Years in Khairunnisa Kindergarten - Yahdi Kumulloh Siregar; Nurhafizah Nurhafizah (Universitas Pendidikan Indonesia Kampus Serang, 2022)
The problems in this research were backgrounded by preliminary observations results on the use of gadgets which caused inhibition of emotional development of children aged 5-6 years in Khairunnisa kindergarten in Lubuk Sikaping district, Pasaman regency. The purpose of this study was to determine the effect of gadget use on the emotional development of children aged 5-6 years in Khairunnisa kindergarten. This research method is quantitative with a descriptive approach. The population of this study was 25 children aged 5-6 years in Khairunnisa Kindergarten divided into 2 study groups, namely group B1 (13 children) and group B2 (12 children). The data was gained with a questionnaire and was analyzed using quantitative descriptive techniques including frequency and percentage. The results of this research showed that the influence of gadget use on the emotional development of children aged 5-6 years in Khairunnisa kindergarten had a percentage of 72.2% in the influential category. The influence of gadget use on the emotional development of children aged 5-6 years can be seen through 4 sub-variables: (1) self-awareness, (2) responsibility, (3) prosocial behavior, and (4) duration of gadget use. These four variables had different percentages in which indicator 1 had 77.5%, indicator 2 had 74.3%, indicator 3 had 71.5 %, and indicator 4 had 65.5%. This result suggested that parents need to supervise more their children regarding their gadget use since specifically more than 2 hours per day of use tend to cause some aspects of children's emotional development to be hampered incorrectly